Kierkegaard - Zuidema, S. U. 1906-1975 (International library of philosophy and theology. Modern thinkers series, 1960)
Without entering into the issue in detail it seems apparent to us that Kierkegaard developed his idea of existence in order to answer questions raised in his struggle to become a Christian. But this does not imply, in any way, that this idea of existence is essentially dependent upon the idea of Absolute Paradox. As a matter of fact Kierkegaard must do violence to his idea of existence in order to unite it with the idea of Absolute Paradox. Likewise it is our intention to show that Kierkegaard in many points had to pervert the biblical revelation concerning Christ in order to make it compatible with his idea of the Absolute Paradox. Kierkegaard distorted biblical revelation to fit his own preconceived theory of human existence, a theory developed independently of revelation. - Introduction.